Exome Sequencing of individuals with vitiligo and their relatives with and without autoimmune disorders - Rabinda, Kentie Rofhiwa (University of the Witwatersrand, Johannesburg, 2023)
Autoimmune disorders result from the immune system attacking and damaging its healthy cells because of an acquired immune system malfunction. Vitiligo is an example of an autoimmune disorders. It is a common depigmentation skin disorder with an estimated prevalence of 0.5–2% of the population worldwide. It is shown by selective loss of melanocytes causing non- scaly, chalky-white macules. Individuals with vitiligo often have other autoimmune disorders or first-degree relatives with at least one other autoimmune disorder. This study aimed to identify genetic variants in selected genes in individuals with vitiligo and their unaffected close relatives who have other autoimmune disorders. Upon DNA extraction, whole exome sequencing was performed, and five non- major histocompatibility complex (MHC) genes were analysed. Identified variants were annotated on Ensembl Variant Effect Predictor (VEP) and compared between individuals with vitiligo and their close relatives with and without autoimmune disorders in a family-specific manner. Eight variants were identified in two families, however, the three missense variants in the NLRP1 gene (rs12150220, rs11651270, and rs2301582) were observed between and across two families in individuals with autoimmune disorders. SMOC2 rs13208776, was identified as a risk locus for vitiligo in individuals from two Romanian isolate villages with vitiligo and other autoimmune disorders. None of the genotyped individuals were homozygous for the minor allele (A) and 2/12 individuals were heterozygous therefore it is unlikely that rs13208776 has any role in the development of vitiligo or any of the autoimmune disorders present in the two families. This study showed that NLRP1 gene variants segregated with vitiligo and autoimmune disorders
A research report (in the format of a “submissible” paper) submitted in partial fulfillment of the requirements for the degree of Master of Science in Medicine (Genomic Medicine) to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg 2023
Keywords: Autoimmune disorders; Vitiligo; Non-major histocompatibility complex(MHC) genes; Whole exome sequencing; UCTD; SDG-3: Good health and well-being